A Evaluation of Placentrex as a novel storage medium for avulsions: an invitro study - Patil, Anand; S.B, Apporva; T.M , Mangla; Saraf, Prahlad; Chincholi, Rashmi (International Journal of Scientific Research and Management (IJSRM), 2021)
ABSTRACTTooth avulsion is one of the common traumatic injury results in complete extrarticulation of tooth from its socket since resulting in damage to the periodontal tissues. Maintaining viability of the periodontal cells remains a challenge to the clinician to reimplant the avulsed tooth. Since various avulsion media are used in dentistry a novel medium Placentrex derived from 0.1 gm. of fresh term, sterilized, infection-free human placenta which has unique pharmacological effects like enhancement of wound-healing, anti-inflammatory, antioxidant and analgesic effect is compared with HBSS and Propolis media in freshly extracted, non carious, non restored, periodontal diseases free human teeth which are indicated for orthodontic treatment purposes were used. The extracted teeth were placed in the enzyme solution to facilitate detachment of the cells and after ten minutes teeth were removed and 1 ml of solution were collected through micropipette and centrifuged. The stained cells were counted in Neubauer’s chamber under a light microscope at 10× magnification. Conclusion: Placentrex maintained PDL cell viability almost similar to Propolis and significantly better than HBSS. KEY WORDS : Avulsions, Avulsion media, HBSS, Reimplantation,